Peningkatan Maharatul Kalam Mahasiswi Sekolah Tinggi Ilmu Tarbiyah Diniyyah Puteri Melalui Metode Taqdimul Qissah - Sulasmi, Sulasmi; Sartika, Diana; Wahyuni, Sri Intan; Lestari, Mega Cahya Dwi; Dewi, Ayu Citra (Institut Agama Islam Sumatera Barat, 2023)
Arabic requires four competencies in its mastery, maharatul istima', maharatul kalam, maharatul qira'ah and maharatul kitabah. In Maharatul Kalam which is a practical ability in speaking, STIT Diniyyah Puteri Rahmah El Yunusiyyah still does not show maximum mastery, this is evidenced by the lack of conversation used in Arabic and also the use of rules that are not appropriate when speaking. This can be seen from the initial observation value made by lecturers showing an achievement of 42%. This type of research is a class action research (PTK) and is carried out at STIT Diniyyah Puteri Rahmah el Yunusiyyah Padang Panjang. With the subject of research for 5th semester female students of the PAI Study Program for the academic year 2022-2023, consisting of 12 students. The instrument used is an observation sheet on the improvement of maharatul kalam carried out directly by the eye-supporting lecturer as well as the researcher. The results of this study show that the application of the Taqdimul Qissah method can improve speaking skills in semester 5 of PAI STIT Diniyyah Puteri Rahmah el Yunusiyyah. The increase can be seen from the average score of maharatul kalam through taqdimul qissah without props, which is 57.10%. Then by using the media props that have been prepared, both in the form of pictures displayed such as playing puppets, as well as props worn directly as clothes by the narrator can increase enthusiasm in learning so that there is a more significant increase in the second cycle, which is 82.21%.